Pengaruh Kualitas Pelayanan dan Kepuasan Nasabah Terhadap Loyalitas Nasabah di Bank Mandiri KCP Jamika Bandung - Hengki Febrianto; Ramayani Yusuf (Universitas Batanghari Jambi, 2021)
This study entitled the influence of service quality and customer satisfaction on customer loyalty at PT. Bank Mandiri KCP Jamika Bandung. This study aims to determine the effect of service quality and customer satisfaction on customer loyalty at PT. Bank Mandiri KCP Jamika Bandung. Researchers used quantitative methods with a descriptive approach. Data collection techniques using questionnaires, interviews, and literature study. The sample size was taken as many as 87 respondents. The results of this study found that the service quality has a partial effect of 0.000 <0.05. In addition, customer satisfaction does not have a partial effect of 0.325 > 0.05. For service quality and customer satisfaction have a simultaneous effect with the obtained f-table value has a large effect 59.24 > 3.11 on customer loyalty. Thus, the coefficient of determination obtained at the R square value is 0.587 or 5.87% with the remaining 41.3% caused by other elements that are not present in this study at PT. Bank Mandiri KCP Jamika Bandung.